On the issue of the 'Kazan Chronicle' as a literary source of M.M. Kheraskov's poem 'Rossiada' - A.I. Zavyalova (Ученые записки Казанского университета: Серия Гуманитарные науки)
M.M. Kheraskov’s epic poem “Rossiada” is devoted to the Kazan Siege by Ivan the Terrible. It is based on the works published by Russian historians, as well on facts from the Old Russian manuscripts. One of the main literary sources of the “Rossiada” is the “Kazan Chronicle”, also known as the “Story of the Tsardom of Kazan”, a famous historical and publicistic story of the 16th century. This hypothesis was introduced as a result of the studies by G.Z. Kuntsevich, U.N. Sidorova, and G.N. Moiseeva. In this paper, the authenticity of the hypothesis was considered. Comparative study of the “Rossiada” and different sources about the Kazan Siege was performed. The Old Russian manuscripts and the “Kazan Chronicle” also contain numerous stories about the Kazan Siege. New facts confirming that the “Kazan Chronicle” was used by M.M. Kheraskov to create the plot of his epic poem were discussed: he drew upon some historical facts, such as about the Tartarian princess Söyembikä and the Kazan voivode Atalyk. The writer imitated the attitude of the author of the “Kazan Chronicle” towards the characters. Therefore, the “Kazan Chronicle” turns out to be the most important source of M.M. Kheraskov’s poem, but not the only one.